Hubungan Beban Kerja Dengan Kelelahan Pada Pekerjadi PT.Mutiara Pesona Abadi Kota Mojokerto - Arief fardiansyah; Elok Miftachul Jannah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
Every worker has the right to obtain protection for occupational health and safety. Each person's workload is different depending on their abilities. If a person's workload is excessive, it can cause work fatigue. Work fatigue can cause decreased physiological functions, decreased performance, decreased company productivity and accidents to workers. The purpose of this study was to determine the relationship between workload and fatigue on workers at PT.Mutiara Pesona Abadi, Mojokerto City. The research method used was observational analytic and cross sectional research design. The population in this study were 34 people using total sampling technique. The instrument used to measure fatigue is the Subjective Self Rating Test (SSRT) questionnaire adopted from the Industrial Fatigue Research Committee (IFRC) Japan consisting of 30 questions and measuring workload with pulse that is carried out before and during work then calculated using the Cardiovascular Load formula (CVL). The results showed that almost all workers experienced moderate workload as many as 26 respondents (76.5%) and almost all workers experienced moderate work fatigue as many as 31 respondents (91.2%). Analysis of the data used in this study using the Spearman Rank Test with a p value of 0.001 so that it can be concluded that a <0.05 then there is a relationship between workload and fatigue on workers at PT.Mutiara Pesona Abadi, Mojokerto City. The company is advised to rearrange the workplace to be better to create comfort so as to increase productivity and workers are expected to optimize rest hours to recover energy. ..